Respostas
respondido por:
3
x²+2xy+y = x(x+2y) + y
4x²+8xy+4y² = (a+b)(a+b) = (2x+2y)(2x+2y) = (2x+2y)²
4x²+8xy+4y² = (a+b)(a+b) = (2x+2y)(2x+2y) = (2x+2y)²
respondido por:
1
Oi,
Resolução:
Decompondo
a)
x^2 + 2xy + y
x * ( x + 2y ) + y
b)
4x^2 + 8xy + 4y^2
4 * ( x^2 + 2xy + y^2 )
Espero ter ajudado e bons estudos !
Resolução:
Decompondo
a)
x^2 + 2xy + y
x * ( x + 2y ) + y
b)
4x^2 + 8xy + 4y^2
4 * ( x^2 + 2xy + y^2 )
Espero ter ajudado e bons estudos !
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás